IMPLEMENTATION OF AKAD AL-WAKALAH IN ECONOMIC TRANSACTIONS IN SHARIA FINANCIAL INSTITUTIONS - Iwan Permana; Uus Putria (Univeristas Islam Bandung, 2022)
Akad Al-Wakalah is the result of innovation from Islamic economic thinkers for ease in conducting economic transactions in sharia financial institutions, therefore akad wakalah is a product of ijtihad born of research on the Qur'an and the Hadiths of the Prophet, for the benefit of transactions economy then was born the covenant of al-Wakalah. The purpose of this research is to explain the interpretation, implementation, and validity of the al-Wakalah in sharia financial institutions. The research method used is a qualitative method by using a descriptive analysis approach. The results show the validity of economic transactions using the al-Wakalah and become a regulation for the Shariah Financial Institution.